Non-Governmental Organization's (NGOs) contribution towards community development education : a case study - Chelliah, Nagarajan (1997)
This study attempted to outline and describe how non-governmental organisastions (NGOs) can effectively contribute to the community development education of the urban poor and the plantation communities in the country. This is a qualitative study using the case study design. A local non-governmental organisation: Alaigal was chosen for this case study. The first part of the study explained the contribution of various NGOs all over the world, especially highlighting their activities and contribution towards community educational development. The objective of this study was to outline the growth of Alaigal; list out the programmes and how these programmes brought self-awareness and community education development to the respective communities. The data collection was done by interviewing the Alaigal committee members and the resident committee members such as Kg. Chekkadi. Observation and participation in some of their programmes and documents such as articles from magazine Alaigal's publications and seminar papers provided more information.Alaigal's programmes were community activities in Kg. Chekkadi, Klabang Estate and Kg. Jelapang Barn and networking activities with other NGOs such as Rural Development program, Election Campaign and Wage referendum campaign. Other programmes include social programmes for the urban poor and plantation communities and providing consultancy and advocacy services to those facing industrial problems such as SOCSO benefits, unfair dismissal and others. These activities were documented by observation and interviewing. The books, pamphlets and newsletters published by Alaigal, made the community to be aware of the problems faced by a section of the people in our society. These programmes brought self-awareness among the members of the society who are who are now aware and ready to seek for their basic rights in a democracy way. These programmes and publications provided non-formal education and self-awareness which helped to empower the members of the communities to achieve self reliance and community development.The services provided by NGOs supplement the governments effort in bringing about economic growth and community educational development to the marginalized communities. Thus, government should encourage and foster the growth of NGOs in the country for the development and prosperity of the nation.